PS02.231: RELATIONSHIP BETWEEN CHANGE IN TONGUE PRESSURE AND PNEUMONIA AFTER ESOPHAGECTOMY. (14th September 2018) - Yokoi, Aya; Ekuni, Daisuke; Yamanaka, Reiko; Morita, Manabu
Abstract: Background: Esophagectomy for esophageal cancer is a highly invasive procedure with several serious postoperative complications, including pneumonia. It is commonly accepted that deteriorated swallowing function causes postoperative pneumonia. However, measurement to evaluate swallowing function related to postoperative pneumonia has not been developed. Recently, it became possible to measure tongue pressure using a non-invasive, easy and portable device. We hypothesized that tongue pressure relates to postoperative pneumonia. The aim of this study was to investigate the relationship between change in tongue pressure and pneumonia after esophagectomy among inpatients with esophageal cancer. Methods: Fifty-eight inpatients (39 males and 19 females; 33–77 years old) who underwent esophagectomy participated in this study. Measurement of tongue pressure was performed using a portable device before esophagectomy (baseline) and at postoperative 1 and 2 weeks. Repetitive saliva swallowing test (RSST) was also performed to evaluate swallowing function at the same time. Pneumonia was postoperatively diagnosed by the chest X-ray, white blood count, body temperature and purulent sputum. The data of general and oral conditions were collected from medical and dental records. Data also included sex, age, type of cancer, cancer stage (International Classification of Diseases for Oncology ICD-10 version 2015), type of operation (thoracotomy or thoracoscopy), type of preoperative chemotherapy, surgical duration, amount of bleeding during surgery, type of reconstruction, incidences of postoperative complications, intubation period, body temperature, blood chemical analysis, health behaviors and oral condition. Differences in parameters between the pneumonia (+ ) group (n = 10) and pneumonia (-) group (n = 48) were analyzed by Mann-Whitney U or Chi-square test. Level of significance was set at P < 0.05. Results: Tongue pressure significantly decreased after esophagectomy ( P < 0.05). The decrease in tongue pressure, age, amount of bleeding during surgery, length of fasting days, the ratio of thoracotomy and aspiration in the pneumonia (+ ) group were significantly greater than those in the pneumonia (-) group ( P < 0.05). Conclusion: The decrease in tongue pressure was related to the incidence of pneumonia after esophagectomy among inpatients with esophageal cancer. Disclosure: All authors have declared no conflicts of interest.